A study on organisational culture and it’s impact on employees’ behaviour in automobile industry - M, Sirajudeen; Irshath, Mohamed; S, Tamilenthi (International Multidisciplinary Research Journal, 2012)
The study brings out the behavioural aspect of the employees working in Hyundai Motors India Ltd. The main objective of the study is to find the overall performance of the employees. The study is descriptive research with the sample of 100 employees working in Hyundai Motors India Ltd. Data was collected by survey method through structured questionnaire with close ended questions. The primary data was obtained through questionnaire and secondary data from the company records and websites. The purpose of the survey process is to provide a more accurate assessment of the existing culture from the employees’ point-of-view and also to assess their behaviours with respect to that of the existing culture. The culture of an organization consists of the values and beliefs of the people in an organisation. The organisational culture usually has values and beliefs that support the organisational goals. Organizational culture has an impact on employee’s satisfaction. The analysis was done through simple percentage analysis and weighted average method. From the analysis it was found that the employees of HMIL were much satisfied with their interpersonal relationships, co-ordination and integration between various departments of the organization, and also the rewards & incentives given by their management. But the management has to provide more practical sessions in training programmes to improve their performance in their respective fields. Such training programmes will help them to enhance their knowledge in the respective fields.